A microextraction procedure based on an ionic liquid as ion-pairing agent optimized using a design of experiments for chromium species separation and determination from water samples - Berton, Paula (2013)
A microextraction methodology based on a room temperature ionic liquid (IL) as an ion-pairing reagent for determination of trace Cr(III) and Cr(VI) species is proposed. First, an ion-pair was formed between Cr(VI) species and the hydrophobic IL trihexyl(tetradecyl)phosphonium chloride (CYPHOS IL 101). A simple and rapid microextraction procedure named ultrasound-assisted emulsification-microextraction (USAEME) was then developed for Cr species separation and preconcentration. Determination of Cr was performed by direct injection of the organic phase into an electrothermal atomic absorption spectrometer (ETAAS). Parameters that affect the efficiency of the microextraction step were investigated using a Plackett? Burman screening design. Then, the variables showing significant effects on the analytical response were considered within a further central composite design to optimize the experimental conditions. For 10 mL of water sample, the optimized USAEME procedure used 40 mL of tetrachloroethylene as extraction solvent, 5 min of extraction and 5 min of centrifugation at 1700 rpm. Selectivity among Cr species was obtained through pH selection. The concentration of Cr(III) species was calculated from the difference of total Cr and Cr(VI) concentrations. Under optimum conditions, the analyte extraction recovery was higher than 99% and yielded a preconcentration factor of 250. The limit of detection (LOD) obtained was 14.8 ng/L and the relative standard deviation for 10 replicate determinations at the 0.05 mg/L Cr(VI) level was 3.8%, calculated at peak areas. A correlation coefficient of 0.9983 was achieved. The method was successfully applied for Cr species determination in tap and river water samples.